International Society of Paediatric Oncology (SIOP) Global Mapping Programme: Latin American Society of Pediatric Oncology (SLAOP) country-level report - Cappellano, A (2024)
Background: Latin American countries are improving childhood cancer care, showing strong commitment to implement the Global Initiative for Childhood Cancer, but there are scant publications of the situation at a continental level. Methods: As part of the International Society of Paediatric Oncology Global Mapping project, delegates of each country participating in the Latin American Society of Pediatric Oncology (SLAOP) and chairs of national pediatric oncology societies and cooperative groups were invited to provide information regarding availability of national pediatric cancer control programs (NPCCP), pediatric oncology laws, pediatric oncology tumor registries, and training programs and support to diagnosis and treatment. Results: Nineteen of the 20 countries participating in SLAOP responded. National delegates reported nine countries with NPCCP and four of them were launched in the past 5 years. National pediatric tumor registries are available in eight countries, and three provided published survival results. Fellowship programs for training pediatric oncologists are available in 12 countries. National delegates reported that eight countries provide support to most essential diagnosis and treatments and 11 provide partial or minimal support that is supplemented by civil society organizations. Seven countries have a pediatric oncology law. There are three international cooperative groups and four national societies for pediatric oncology. Conclusion: Despite many challenges, there were dramatic advances in survivorship, access to treatment, and availability of NPCCP in Latin America. Countries with highest social development scores in general provide more complete support and are more likely to have NPCCP, training programs, and reported survival results.